Comparison of Caputo and conformable derivatives for time-fractional Korteweg-de Vries equation via the finite difference method - Yokus, Asif (World Scientific Publ Co Pte Ltd, 2018)
In this study, we investigate the nonlinear time-fractional Korteweg-de Vries (KdV) equation by using the (1/G')-expansion method and the finite forward difference method. We first obtain the exact wave solutions of the nonlinear time-fractional KdV equation. In addition, we used the finite-forward difference method to obtain numerical solutions in this equations. When these solutions are obtained, the indexed forms of both Caputo and conformable derivatives are used. By using indexing technique, it is shown that the numerical results of the nonlinear time-fractional KdV equation approaches the exact solution. The two- and three-dimensional surfaces of the obtained analytical solutions are plotted. The von Neumann stability analysis of the used numerical scheme with the studied equation is carried out. The L-2 and L-infinity error norms are computed. The exact solutions and numerical approximations are compared by supporting with graphical plots and tables.
Keywords: Caputo derivative; conformable derivative; time-fractional Korteweg-de Vries equation; finite difference method; traveling wave solution